PERCEPTIONS OF SEXUAL BEHAVIOR AND KNOWLEDGE ABOUT SEXUALLY TRANSMITTED INFECTIONS AMONG YOUNG PEOPLE IN TIRANA, ALBANIA - Subashi, Anisa (European Scientific Journal, ESJ, 2014)
The level of sexual activity and the incidence of sexually transmitted diseases (STDs) are high among Albanian young people, but use of reproductive health services is low. Information about their attitudes and experiences is needed for the design of youth-friendly programs.30 focus group discussions were conducted among young people aged 14-19 attending gymnasiums in Tirana City. The discussions explored the adolescents’ perceptions of sexual behavior among their peers, their knowledge of STIs and their preferred means of preventing and treating STIs. The participants perceived that sexual activity is common among their peers. They noted that although physical attraction is the main reason for romantic relationships (which might include sex), the desire for material or financial gain is the primary motivation for sexual relationships. The young people had some knowledge about STIs, especially HIV and AIDS, but many believed infections were inevitable. When they had an STI, non educated young people went to traditional healers; they were unlikely to seek treatment from doctors because of high cost, slow service, negative provider attitudes toward young people and a perceived lack of confidentiality. The participants considered media campaigns as the best way to educate young people about STIs and condom use.